2015
DOI: 10.1210/me.2014-1289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypothalamic Arcuate Nucleus-Specific Enhancer Region of Kiss1 Gene in Mice

Abstract: Pulsatile secretion of GnRH plays a pivotal role in follicular development via stimulating tonic gonadotropin secretion in mammals. Kisspeptin neurons, located in the arcuate nucleus (ARC), are considered to be an intrinsic source of the GnRH pulse generator. The present study aimed to determine ARC-specific enhancer(s) of the Kiss1 gene by an in vivo reporter assay. Three green fluorescent protein (GFP) reporter constructs (long, medium length, and short) were generated by insertion of GFP cDNA at the Kiss1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
5
21
0
Order By: Relevance
“…The bidirectional regulation of Kiss1 expression by estrogen might be mediated by ERα, because estrogen changes AVPV or ARC Kiss1 expression in ovariectomized ERβ knockout mice, but not in ERα knockout mice [60]. Recent advances in epigenetic research for the regulation of Kiss1 expression [68, 69] provide a clue as to how estrogen regulates Kiss1 expression in these two hypothalamic regions in a different manner. In the AVPV, estrogen-ERα complexes, which are highly recruited at the Kiss1 promoter, are likely involved in the histone acetylation of the Kiss1 promoter and the subsequent Kiss1 expression by a chromatin loop formation between the Kiss1 promoter and the 3′-downstream enhancer region [68].…”
Section: Hypothalamic Kisspeptin Neurons Control Gnrh Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bidirectional regulation of Kiss1 expression by estrogen might be mediated by ERα, because estrogen changes AVPV or ARC Kiss1 expression in ovariectomized ERβ knockout mice, but not in ERα knockout mice [60]. Recent advances in epigenetic research for the regulation of Kiss1 expression [68, 69] provide a clue as to how estrogen regulates Kiss1 expression in these two hypothalamic regions in a different manner. In the AVPV, estrogen-ERα complexes, which are highly recruited at the Kiss1 promoter, are likely involved in the histone acetylation of the Kiss1 promoter and the subsequent Kiss1 expression by a chromatin loop formation between the Kiss1 promoter and the 3′-downstream enhancer region [68].…”
Section: Hypothalamic Kisspeptin Neurons Control Gnrh Secretionmentioning
confidence: 99%
“…In the AVPV, estrogen-ERα complexes, which are highly recruited at the Kiss1 promoter, are likely involved in the histone acetylation of the Kiss1 promoter and the subsequent Kiss1 expression by a chromatin loop formation between the Kiss1 promoter and the 3′-downstream enhancer region [68]. In the ARC, histone acetylation of the Kiss1 promoter and a chromatin loop formation between the Kiss1 promoter and the 5′-upstream enhancer region seems to be involved in Kiss1 expression in the absence of estrogen [68, 69]. Taken together, histone acetylation of the Kiss1 promoter is positively correlated with Kiss1 expression in both hypothalamic nuclei, and region-specific enhancers serve as switches for the bidirectional regulation of Kiss1 expression (Fig.…”
Section: Hypothalamic Kisspeptin Neurons Control Gnrh Secretionmentioning
confidence: 99%
“…Goto et al [14] found ARC-specific chromatin loop formation between the promoter region and the 5′ upstream region of the Kiss1 gene, suggesting that the 5′ upstream region of the Kiss1 gene plays a key role in upregulating Kiss1 gene expression as an enhancer in the ARC. This study also showed a binding of unoccupied ERα and putative transcriptional factor binding sites in the ARC-specific putative enhancer region of the Kiss1 locus.…”
Section: Epigenetic Mechanism Of Estrogenic Regulation Of Kiss1 Gene mentioning
confidence: 99%
“…The assay revealed that the 3′ downstream region of the Kiss1 locus contributes to induction of estrogen-induced AVPV Kiss1 gene expression [11], while the 5′ upstream region of the Kiss1 locus is conducive to ARC Kiss1 gene expression [14]. More specifically, chromatin loop formation between the Kiss1 promoter region and the 3′ downstream region in the AVPV or the 5′ upstream region in the ARC, respectively, may act as a switch, which could turn on Kiss1 gene expression.…”
Section: Epigenetic Mechanism Of Estrogenic Regulation Of Kiss1 Gene mentioning
confidence: 99%
See 1 more Smart Citation